(untitled) (Web of Teachers: Inderscience Research, 2024)
The article sheds light on the attitudes of English teachers in Uzbekistan towards the integration of authentic materials in EFL classrooms, contributing to the ongoing discourse on effective language teaching methodologies and materials. The study delves into when authentic materials should be introduced in language instruction, with contrasting perspectives on their suitability for different proficiency levels. Additionally, it discusses criteria for the selection of authentic texts, emphasizing appropriateness, usability, and cultural relevance. Moreover, the sources of authentic material, including newspapers, magazines, television, video, radio, literature, and the Internet, are explored, with a focus on their accessibility and effectiveness in language learning contexts.